Factors Influencing the Doctor of Medicine Career Choice Intention Among STEM Senior High School Students from a Private Educational Institution in Manila, Philippines - Amparo, Alexa Louise S.; Angeles, Audrey Carmela C.; Cabotaje, Angela Nicole M.; Seno, Marianne Rose T.; Arcinas, Myla M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The purpose of this study was to examine the relationship between career intention to pursue a Doctor of Medicine (MD) and attitudes, social influence (SI), and career self-efficacy (CSE) in STEM SHS students from a private educational institution in Manila, Philippines. The online survey drew a total of 103 purposively selected SHS students. The findings indicate that respondents have a strong intention to pursue a career in medicine, a favorable attitude toward MD careers, a moderate to a high SI, and a high CSE. The Spearman Rho Correlation revealed that their attitude, career self-efficacy, and social influence were all statistically significant factors of their intention to pursue a career in medicine. A positive attitude, combined with a high level of career self-efficacy and supportive family, teachers, and peers, all contribute to a student's decision to pursue a career in medicine.